Development and optimization of a quantum dot-based lateral flow assay for hepatitis B surface antigen detection - Abu, Norhidayah; Saari, Norhafizah; Abdullah, Jaafar; Shueb, Rafidah Hanim (American Chemical Society, 2026)
Early detection of hepatitis B virus (HBV) is essential for effective disease management, particularly in cases involving low viral loads where timely intervention can prevent chronic progression and liver-related complications. Although enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) are considered the gold standards for HBV detection, their reliance on specialized infrastructure limits their accessibility in resource-limited settings. This study reports the development and optimization of a cadmium quantum dots-based lateral flow assay (cadmiumQDs-LFA) for the detection of hepatitis B surface antigen (HBsAg), harnessing the superior fluorescence properties of cadmiumQDs to improve analytical performance. Compared to conventional gold nanoparticles (AuNPs)-based LFA, cadmiumQDs exhibit higher fluorescence intensity and stability, enabling improved sensitivity for detecting low-abundance biomarkers. Commercially sourced cadmiumQDs were functionalized with mercaptopropionic acid (MPA) to introduce carboxyl (−COOH) functional groups for bioconjugation. The optimized cadmiumQDs conjugates were integrated into an LFA, achieving a limit of detection (LOD) of 15.6 ng/mL for HBsAg. Performance evaluation using 244 clinical serum samples yielded a sensitivity of 86.5%, specificity of 95.9%, positive predictive value (PPV) of 98% and negative predictive value (NPV) of 75.3%. Comparative analysis with a commercial LFA demonstrated enhanced detection of low HBsAg levels, addressing a key limitation of conventional methods.